PENGARUH NILAI-NILAI TUNJUK AJAR UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 10 PEKANBARU - Andrayani, Nini; Saam, Zulfan; Rosmawati, Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: One important aspect of personality is self-confidence. Self-confidence is one of the key parts of the success of one's life. This study aims to determine the description of students 'self-confidence before and after being given Tunjuk Ajar Values through group guidance, knowing the differences in the level of self-confidence of students before and after Tunjuk Ajar Values through group guidance and to determine the influence of Tunjuk Ajar Values increase student confidence through group guidance. This research is a quantitative research with experimental methods, the research design used is Pre-Experimental approach with one group pre-test and post test subjects in this study were 7 students taken by purposive sampling technique with the criteria of students who have low self-confidence. The results showed that: (1) the confidence of students before being given Tunjuk Ajar Values through group guidance was mostly in the low category and after being given Tunjuk Ajar Values through group guidance most were in the high and medium categories. (2) There is a significant difference in the level of self-confidence of students before and after being given Tunjuk Ajar Values through group guidance. (3) There is a significant effect of Tunjuk Ajar Values to increase students' self-confidence through group guidance.Key Words: Tunjuk Ajar Values, Self-Confidence, Group Guidance